Cingulin, Claudin-5 And Tricellulin As A Novel Biomarker For Autism Spectrum Disorder (International Journal of Environmental Sciences, 2025)
Background: Autism spectrum disorder is a complex, heterogeneous developmental disorder, typically diagnosed in early childhood. Genetic, prenatal, and environmental factors all play a role in the development of autism. It can present at various levels of severity, from mild to severe, and has a male preponderance. Key symptoms of ASD include deficits in social communication, restricted interests, and repetitive behaviors.In recent years, the prevalence of ASD has been steadily increasing, raising significant concerns regarding its causes, diagnosis, and effective management. In ASD, the word (spectrum) stands for a wide range of symptoms and to what extent these symptoms progress, and the degree of symptoms development.Given that ASD is associated with neurological dysfunction, this study highlights the importance of analyzing specific tight junction proteins therefore; Cingulin, Claudin-5, and Tricellulin proteins were examined to explore their potential role in the pathogenesis of ASD.Aim of the study: The study aims to determine whether there is a difference in serum levels of Cingulin, Claudin-5, and Tricellulin between children diagnosed with Autism Spectrum Disorder and healthy controls.Materials and methods: The research was conducted as a case-control study over four months from November 2024 to February 2025 at specialized autism centers and a pediatric hospital and included a total of 88 participants aged 3-12 years. The participants were categorized into 56 autistic children (41 males, 15 females) and 32 healthy controls (23 males, 9 females). Blood samples were collected and analyzed for biochemical markers (CGN, CLDN-5, and TRIC) alongside certain vitamins and minerals. Official approval was obtained from the autism centers before the commencement of the study, and verbal consent was secured from the families of autistic children, who voluntarily participated in the study by completing the questionnaire form.Data analysis employed the Mann-Whitney U tests, Pearson's chi-squared test, Spearman's correlation test, Univariate and multivariable logistic regression, and ROC analysis. All P values less than 0.05 were considered statistically significant.Results: Among the total 88 participants—ASD group (n = 56) and control group (n = 32)—the median age (IQR) was 6 years (4–8). The median age at symptom onset was 2 years (IQR: 1.5–4).The median (IQR) concentration of Cingulin (ng/mL) was lower in the ASD group compared to the healthy control group, but this difference was not statistically significant (0.13 [0.08–0.24] vs. 0.15 [0.09–0.30]; p = 0.3). Claudin-5 (pg/mL) showed a significantly lower median (IQR) in the ASD group compared to the healthy control group (32.22 [16.85–48.70] vs. 60.93 [40.93–96.30]; p < 0.001). Similarly, Tricellulin (ng/mL) also showed a significantly lower median (IQR) in the ASD group compared to healthy controls (0.23 [0.09–0.47] vs. 0.42 [0.22–0.69]; p = 0.027).Conclusion and Recommendations: Claudin-5, Cingulin, and Tricellulin levels were significantly lower in the ASD group compared to the control group, suggesting a potential association between tight junction protein dysfunction and ASD pathophysiology. Further detailed and comprehensive longitudinal studies are needed to determine whether altered levels of Claudin-5, Cingulin, and Tricellulin are a cause or consequence of the disease process in ASD.